Pengaruh Efektivitas Penerimaan Retribusi Pengujian Kendaraan Bermotor (PKB) dan Efektivitas Penerimaan Retribusi Terminal Terhadap Efektivitas Pendapatan Dinas Perhubungan Kota Bandung Periode 2019-2022 - Tiara Gadis Riyanti; Citra Sukmadilaga (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This research aims to determine the effect of the effectiveness of receiving motor vehicle testing retributions (PKB) and the effectiveness of receiving terminal retributions on the effectiveness of the Bandung City Transportation Department's revenue for the 2019-2022 period. The population in this research is the Bandung City Transportation Department budget realization report. The sample in this research is the budget realization report for the Bandung City Transportation Department for 48 months during the 2019-2022 period (time series). The method used in this research is a quantitative method with secondary data. The data analysis technique used is the classical assumption test, multiple linear regression analysis and then hypothesis testing using IBM SPSS Statistics 23. The research results show that partially the effectiveness of receiving PKB retributions (X1) has a negative effect on the income of the Bandung City Transportation Department, while the effectiveness of retributions receiving terminal (X2) does not have a positive effect on the income of the Bandung City Transportation Department. Simultaneously, the effectiveness of receiving PKB retributions and the effectiveness of receiving terminal retributions have a positive effect on the effectiveness of the Bandung City Transportation Department's revenue.